THE EFFECTIVENESS OF EDUCATIONAL GAME METHODS USING SPINTA AND FLASHCARD MEDIA AGAINST HANDWASHING BEHAVIOR ON CHILDREN IN SDN 07 AND 04 CENTRAL BENGKULU - Vella Olivia Dining Vella; Ismiati; Darwis (Poltekkes Kemenkes Bengkulu, 2023)
The proportion of correct hand washing behavior in children aged 10-12 years in Indonesia was on average of only 49.8% in Bengkulu Province showing a low proportion of hand washing behavior with soap correctly with a percentage of 40%, while in Bengkulu Tengah Regency it shows a low proportion of washing hands with soap. hands use soap properly with a percentage of 45%. The low level of proper hand washing behavior with soap is a big problem in Indonesia. This study aims to determine the effectiveness of the game method education using spinta and flashcard media on hand washing behavior in children at SDN 07 and 04 Bengkulu Tengah. This research is a quantitative research with a quasi-experimental method . The design used in this study was a two group pretest-posttest. The analysis in this study was carried out through the Kolmogorof Smirnof test and the Wilcoxon followed by the Mann Whitney. The results of the analysis of the mean after the intervention showed that the mean knowledge, attitudes and actions of the spinta media group was greater than the flashcard group, namely the knowledge of the intervention group 7.59 control group 5.41 attitude intervention group 34.35 control group 29.86 intervention group 4.97 control group 3.84. The results of this study indicate that spinta media is more effective than the flashcard group with knowledge and attitudes p value = 0.000 actions p value = 0.014. It was hoped that teachers will increase their active role in explaining hand washed behavior to students so that they can improve and practice hand washing. In addition, schools can support the implementation of good and correct hand washing.